The Role of the Combination of Islamic Education and Technology in Developing Muslim Competencies and Personalities in the Digital Era - Mukhlis Kaspul Anwar (PT Barkah Ilmi Fiddunya, 2024)
The integration of Islamic education and technology plays a crucial role in developing the competencies and shaping the character of Muslims in the digital era. This study aims to examine how the integration of technology into Islamic education can enhance the quality of learning, expand access to information, and optimize the development of students' character. By utilizing technology, such as digital learning platforms, mobile applications, and social media, Islamic education can be delivered in a more engaging and relevant manner for the younger generation living in the digital world. Technology enables more interactive, flexible, and efficient learning methods while introducing Islamic values that can be applied in daily life in the online space. This study uses a qualitative approach with literature review and interviews to analyze how the combination of Islamic education and technology can support the development of academic competencies, digital skills, and resilient moral character in students. The findings indicate that this integration not only enhances technical skills and religious knowledge but also helps students better understand and apply Islamic teachings in facing the challenges of the modern world. Therefore, the integration of Islamic education and technology holds great potential in preparing a generation of Muslims who are capable of adapting to technological advancements without compromising strong religious values